World of wonders : in praise of fireflies, whale sharks, and other astonishments - Nezhukumatathil, Aimee; Nakamura, Fumi Mini (Minneapolis, Minnesota : Milkweed Editions, 2020)
"A collection of essays about the natural world, and the way its inhabitants can teach, support, and inspire us"--
Catalpa tree -- Firefly -- Peacock -- Comb jelly -- Touch-me-nots -- Cactus Wren -- Narwhal -- Axolotl -- Dancing frog -- Vampire squid -- Monsoon -- Corpse flower -- Bonnet macaque -- Calendars Poetica -- Whale shark -- Potoo -- Cara Cara orange -- Octopus -- Grey cocatiel -- Dragon fruit -- Flamingo -- Ribbon eel -- Questions while searching for birds with my half-white sons, aged six and nine, National Audubon Bird Count Day -- Oxford, MS -- Superb Bird of Paradise -- Red-spotted newt -- Southern Cassowary -- Monarch butterfly -- Firefly (redux).
Keywords: Animals -- Anecdotes; Plants -- Anecdotes; Anecdotes